Cholestatic jaundice in infancy: struggling with many old and new phenotypes - Claudia Mandato; Giada Zollo; Pietro Vajro (BMC, 2019)
Abstract Background Clinical diagnosis of neonatal cholestasis is considered to be an extremely challenging process. Here we highlight the importance not only of the prompt distinction between extrahepatic and intrahepatic cholestasis forms, but also of the precise identification of the latter ones amongst the hotchpotch of recently discovered metabolic/genetic causes. Biliary atresia is considered a surgical emergency in a newborn infant. The rate of success in establishing the bile drainage is in fact a function of the early age when the hepato-portoenterostomy intervention is performed. Intrahepatic cholestasis is due to a broad and more and more puzzling variety of infectious, endocrine, genetic, metabolic and toxic disorders where Gamma-glutamyl transpeptidase serum levels may help for differential diagnosis. Recently established laboratory diagnostic techniques have allowed to discover new causes of neonatal cholestasis. Aim of the Commentary is to go through some of them and bring the focus particularly on the information deriving from the paper by Pinon et al. in this issue of the Journal, which paves the way to the inclusion of the hepatocyte nuclear factor-1-beta deficiency as a new condition to consider in the diagnostic process of the syndromic forms with paucity of intralobular bile ducts. Conclusion Neonatal cholestasis poses diagnostic challenges in practice. Recent advances in the pathophysiology and in molecular genetics together with clinical features, histopathologic findings and careful reasoning remains paramount to put together the pieces of the jigsaw.